Population aging and cross-country redistribution in integrated capital markets - Thomas Davoine (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Population aging challenges the financing of social security systems in developed economies, as the fraction of the population in working age declines. The resulting pressure on capital-labor ratios translates into a pressure on factor prices and production. While European countries all face this challenge, the speed at which their population ages differs, and thus the pressure on capital-labor ratios. If capital markets are integrated, differences in population aging may lead to cross-country spillovers, as investors freely seek the best returns on capital. Using a multi-country overlapping-generations model covering 14 European Union countries, I quantify spillovers and find that capital market integration leads to redistribution across countries over the long run. For instance, GDP per capita would on average be 2.9 %-points lower in Germany in each of the next 50 years if capital markets were perfectly integrated and public debts kept constants with increases in labor income taxes, compared to a closed economy case; by contrast, GDP per capita would on average be 2.1 %-points higher in France, whose population ages slower than in Germany. I also show that pension reforms can change the cross-country redistribution patterns, some countries losing from capital market integration without the reform but winning with it.
Keywords: C68; E60; F41; J11; 330; population aging; pension reforms; capital markets; cross-country spillovers; overlapping-generations modelling